Postpartum Stress and Depression Among Mothers Studying in Private Universities. - พันธ์งาม, ชญาภัทร; ทองเกลี้ยง, ขนิษฐา (Chalermkarnchana Academic Journal, 2025)
This study aims to examine the factors influencing postpartum depression among mothers studying at a private university. A survey research method was employed using a standardized questionnaire on postpartum depression and related factors. The sample consisted of 222 postpartum mothers enrolled at Chalermkarnchana University, selected through purposive sampling. Data analysis included descriptive and inferential statistics such as the Chi-Square Test, Independent Sample t-test, and Multiple Regression Analysis. The findings indicate that family support and income are key determinants of postpartum depression. Furthermore, students who had to work while studying exhibited significantly higher levels of depression compared to those who did not. The study suggests that universities should implement support measures such as psychological counseling and financial assistance to alleviate postpartum depression among student mothers.